The Sadharanikaran Model and Aristotle's Model of Communication: A Comparative Study - Adhikary, Nirmala Mani (Bodhi: An Interdisciplinary Journal, 1970)
This article seeks to study the fundamental differences between the Sadharanikaran model and Aristotle's model of communication. The effort here is aimed for having a comparative study of the concepts of communication process envisioned in two different models from the East and the West. The general objective here is to comprehend the fundamental differences between the concepts of communication process in Aristotelian and Sadharanikaran view. The specific objectives include having comparative understanding of the concept of communication process from Aristotelian and Sadharanikaran perspectives in terms of structure and scope of two models, the human relationships in the process and the goal of communication. DOI: 10.3126/bodhi.v2i1.2877 Bodhi Vol.2(1) 2008 p.268-289
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEyNi9ib2RoaS52MmkxLjI4Nzc